Resistance of Fasciola hepatica against Triclabendazole in cattle in Cajamarca (Peru): A clinical trial and an in vivo efficacy test in sheep - Ortiz-Oblitas, P. (2013)
Fasciolosis caused by Fasciola hepatica, is the most prevalent parasitic disease in dairy cattle from the northern region of Cajamarca, Peru. The control of this parasite is based on the use of Triclabendazole (TCBZ), a drug that has been used for more than fifteen years in this area. Recent studies, however, have reported a lack of clinical efficacy after treating dairy cattle. This research was aimed to determine the efficacy of TCBZ in a clinical trial. Eleven dairy cows all positive to F. hepatica identified by presence of eggs in feces, were treated with TCBZ (Fasinex® 10%) at 12 mg/kg body weight. Fourteen and thirty days after treatment, the animals were analyzed for F. hepatica eggs in their feces by the fecal egg count reduction test. The results found show an overall efficacy of 31.05% and 13. 63% (14 and 30 days post treatment, respectively). Furthermore, an in vivo efficacy test was conducted in sheep with metacercariae obtained from eggs isolated from a cow clinically resistant to TCBZ. Eleven sheep divided in two groups, a control group with no treatment (n = 5) and a treated group (n = 6) were all infected with two hundred metacercariae. One hundred and six days after infection all the animals demonstrated F. hepatica eggs in their feces, confirming the presence of adult parasites in their livers. The animals were then treated with TCBZ (Fasinex® 10%) at 10 mg/kg body weight. Fifteen days later, the animals were sacrificed and the number of F. hepatica in their livers counted. The results of this experiment showed an efficacy of the flukicide of 25.2% confirming the resistance to TCBZ of the F. hepatica isolated from dairy cattle in Cajamarca, Peru.